Carrying the Elephants - Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2022)
The big picture is unambiguous: humanity is undermining the planetary ecosystem, and the deterioration continues unhindered. According to the 2019 Global Assessment Report on Biodiversity and Ecosystem Services, since 1970, the capacity of nature to sustain contributions to good quality of life trends downward in 14 out of 18 different categories being analysed, with many species dwindling or becoming extinct. And if this isn't enough, the burning of fossil fuels is believed to alter the climate, most likely for the worse. At stake, then, is the survival of planetary life as we know it, humanity included. And in this dire context, it is worthwhile reading Roman Gary's great 1956 novel, The Roots of Heaven (translated into English in 1958). This Goncourt Prize book is one of the first `ecological novels'. It tells the story of a Frenchmen, Morel, a former concentration-camp prisoner and decorated war hero on a mission to save the hunted elephants of Africa. It is a complex, intellectually gripping story, weaving key issues of the time – from postwar global politics and the nuclear arms race to the clash of colonialism and liberation movements to culture, religion and philosophy – and its broad sweep is narrated with the sensitivity, irony and occasional wishful thinking of a great humanitarian. And it is the book's emphasis on humanity that makes it so important.
Keywords: P16; Q57; 330; ecology; humanity; literature